Endovascular Bailout Repair After Intraprocedural Thrombosis of a Bifurcated Unimodular Stent-graft During Aorto-iliac Revascularization in a Patient with Sars CoV-2 Infection. (July 2023) - Zacà, Sergio; Ramundo, Roberto Maria; Desantis, Claudio; Di Stefano, Lucia; Pulli, Raffaele; Angiletta, Domenico
To describe a case of endovascular bailout strategy during stent-graft thrombotic complication in an endovascular procedure for complex TASC II D aortoiliac lesion. A 77-year-old patient was admitted at our institution with bilateral lower limb rest pain due to aortoiliac obstructive disease in a previous aortobifemoral bypass grafting with an asymptomatic Sars-CoV-2 infection. We planned an anatomic reconstruction of the aortoiliac segment with an unimodular bifurcated stent-graft. During the procedure, we observed a preocclusive thrombosis of the aortic portion requiring endovascular thrombectomy with vacuum assisted system followed by a successfully kissing-stent endolining. The post-operative period was uneventful and patient was discharged on the 14 th post-operative day. Endovascular thrombectomy may be a helpful strategy during thrombotic complication of complex reconstructions of obstructive aortoiliac disease avoiding surgical conversion to laparotomy.